Assessment of Digital PCR as a Primary Reference Measurement Procedure to Support Advances in Precision Medicine. (1st September 2018) - Whale, Alexandra S; Jones, Gerwyn M; Pavšič, Jernej; Dreo, Tanja; Redshaw, Nicholas; Akyürek, Sema; Akgöz, Müslüm; Divieto, Carla; Sassi, Maria Paola; He, Hua-Jun; Cole, Kenneth D; Bae, Young-Kyung; et al.
Abstract: BACKGROUND: Genetic testing of tumor tissue and circulating cell-free DNA for somatic variants guides patient treatment of many cancers. Such measurements will be fundamental in the future support of precision medicine. However, there are currently no primary reference measurement procedures available for nucleic acid quantification that would support translation of tests for circulating tumor DNA into routine use. METHODS: We assessed the accuracy of digital PCR (dPCR) for copy number quantification of a frequently occurring single-nucleotide variant in colorectal cancer ( KRAS c.35G>A, p.Gly12Asp, from hereon termed G12D) by evaluating potential sources of uncertainty that influence dPCR measurement. RESULTS: Concentration values for samples of KRAS G12D and wild-type plasmid templates varied by <1.2-fold when measured using 5 different assays with varying detection chemistry (hydrolysis, scorpion probes, and intercalating dyes) and <1.3-fold with 4 commercial dPCR platforms. Measurement trueness of a selected dPCR assay and platform was validated by comparison with an orthogonal method (inductively coupled plasma mass spectrometry). The candidate dPCR reference measurement procedure showed linear quantification over a wide range of copies per reaction and high repeatability and interlaboratory reproducibility (CV, 2%–8% and 5%–10%, respectively). CONCLUSIONS: This work validates dPCR as an SI-traceable reference measurement procedure based on enumeration and demonstrates how it can be applied for assignment of copy number concentration and fractional abundance values to DNA reference materials in an aqueous solution. High-accuracy measurements using dPCR will support the implementation and traceable standardization of molecular diagnostic procedures needed for advancements in precision medicine.